Leadership Literacy Challenges and Sustainable Transformation in Nigeria - Aderogba, Kofo A (Strukturasi: Jurnal Ilmiah Magister Administrasi Publik, 2025)
The public education system faces several challenges in providing quality literacy education. The work focuses on the role of adult leadership literacy education in achieving sustainable socioeconomic development, exploring how it can be utilized to promote sustainable development. The human condition can be described in terms of the threats to sustainable socioeconomic development, as shaped by the literacy level of Nigerian adult leaders. Like most of the African States, Nigeria is still "backward." The quest for gratuitous needs and greed is peerless. Many common practices can be implemented to encourage literacy and numeracy learning. Adequate and relevant literacy will produce "People’s Leaders.” It would not be out of place for communities, social organizations, the military, and the para-military to embark on appropriate literacy and numeracy programmes.